BUDAYA KORPORAT DAN PRODUKTIVITAS KERJA KARYAWAN PT. BANK RAKYAT INDONESIA (PERSERO) TULUNGAGUNG - Ema Desia Prajitiasari; Thantawi A.S - -; Armanu Thoyib (Sekolah Pascasarjana Universitas Brawijaya, 2009)
In the continuously operational management context and particularly on the long term perspective, human resources have an important role in creating and realizing business opportunities. Producing a high level of integrity among professional employee demands called corporate culture for all participants of the company rely on the base while achieving the task. Competitive advantages of a company is productivity. Objective of this research is to analyze effects of the corporate culture variables (integrity, professionalism, customer satisfaction, pattern, and reward to human resource) simultaneously and partially, on employee’s work productivity. Other analysis emphasizes on dominant influential variables of corporate culture on the employee’s work productivity. Method of Stratified Random Sampling was applied at the PT. Bank Rakyat Indonesia (Persero) Branch Office Tulungagung and select for 118 respondents. Hypothesis examination involves multiple regression analysis. Results of this research indicate that integrity, professionalism, customer satisfaction, pattern, and reward to human resource simultaneously and partially have positive influence on employee’s work productivity. Results also show that pattern has a dominant influence on the employee’s work productivity. Keywords: corporate culture, employee’s work productivity.